Role of National Taxes and Fees in the System of Mandatory Payments - O. V Pabat (Bulletin of Kharkiv National University of Internal Affairs)
The provisions of the Tax Code of Ukraine, which determine the national taxes and fees within the system of mandatory payments, have been studied. It has been determined that the main purpose of national taxes and fees is the formation and saturation of the State budget’s revenues. The influence of national taxes and fees on the regulation of production and consumption has been clarified. It has been stated that national taxes and fees have a general impact on each person, obliging him or her to pay taxes established by the Tax Code. It has been determined that the studied taxes and fees are a lever for regulating and preventing negative tendencies in the economy and are the part of the mechanism that ensures the relationship between national interests and the interests of local business entities. The role of national taxes and fees within the system of mandatory payments as a source of revenues of the State budget (given their stability) also determines the policy of formation of all other types of revenues. The role of national taxes and fees in the formation of local budgets in Ukraine has been analyzed, namely such instruments of budget regulation as interest deductions from national taxes and revenues, budget transfers (budget subsidies, subsidies and subventions, withdrawals to the State Budget of Ukraine, intergovernmental settlements) and budget loans.